2016
DOI: 10.1007/s11892-016-0779-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Youth With Type 1 Diabetes: a Review

Abstract: Youth with type 1 diabetes are at risk for developing cardiovascular disease, and regular physical activity is strongly recommended as one strategy for prevention, as well as for good glycemic control. Despite recommendations, families in this pediatric population face unique barriers to physical activity, including fear of hypoglycemia. Moreover, families are not routinely counseled in the specific health and psychosocial benefits of following physical activity recommendations for youth with type 1 diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 70 publications
2
33
0
Order By: Relevance
“…For children and adolescents specifically, the reduction or elimination of physical education in the school environment and participation in sedentary extracurricular activities reduces participation in physical activity [60]. In addition, loss of T1D control and external temperature are barriers to physical activity for children and adolescents [53].…”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%
“…For children and adolescents specifically, the reduction or elimination of physical education in the school environment and participation in sedentary extracurricular activities reduces participation in physical activity [60]. In addition, loss of T1D control and external temperature are barriers to physical activity for children and adolescents [53].…”
Section: Physical Activity and Individuals With T1dmentioning
confidence: 99%
“…Fear of hypoglycemia appears to be the most common reason to avoid exercise in children and adolescents. Therefore, addressing the appropriate management of insulin regimen and carbohydrate intake is important to avoid these fluctuations in glycemic control for safety and also for reassuring the child/adolescent and families (27,28). Severe hypoglycemia may be related to insulin-dependent and insulin-independent glucose uptake.…”
Section: Hypoglycemia and Hyperglycemiamentioning
confidence: 99%
“…Exercise education provided to patients and families living with type 1 diabetes may focus on the management of blood glucose levels during and after exercise rather than stressing its cardiovascular health benefits and its primary role in the management of type 1 diabetes . However, a review of the literature indicated that increasing provider focus on promoting exercise starting at diagnosis of type 1 diabetes is supported …”
Section: Introductionmentioning
confidence: 99%
“…Studies demonstrate that at least two thirds of children with type 1 diabetes may not be meeting exercise recommendations . This is concerning due to the fact that children with type 1 diabetes have twice the risk of developing heart disease during their lifetime when compared to those without diabetes . According to the American Diabetes Association (ADA) Standards of Medical Care in Diabetes (2019) guidelines, children and adolescents with type 1 diabetes, type 2 diabetes, or prediabetes should participate in moderate to vigorous‐intensity aerobic activity for at least 60 minutes per day, with vigorous muscle‐strengthening and bone‐strengthening activities at least 3 days per week .…”
Section: Introductionmentioning
confidence: 99%